El Derecho español sobre comedores de empresa: actualidad y paradojas - Sempere Navarro, Antonio V. (Revista de Derecho, 2019)
Two rulings dated 1938 established the obligation of companies to make dinners available to their workers, whether this would be in the form of a place arranged for such purpose, or by even serving food. Since then no other state norm has taken care of the matter, discussing whether the old norms are still current. On the other hand, when workers really benefit from the company’s dinner, of lowprice food or of restaurant tickets; all sorts of doubts rise regarding their juridical nature. The present study revises this old institution, examining the most recent sentences and reporting the state of the matter.